Socio-economic and food system drivers of nutrition and health transitions in The Gambia from 1990 to 2017 - Ali, Zakari; Scheelbeek, Pauline F.D.; Dalzell, Sarah; Hadida, Genevieve; Segnon, Alcade C.; M'boob, Sulayman; Prentice, Andrew M.; Green, Rosemary (Elsevier, 2023)
In common with many nations undergoing a nutrition transition, micronutrient deficiencies, undernutrition and overnutrition coexist in The Gambia. Addressing these challenges simultaneously would require transformational changes in the country's food system. However, the evidence base that would enable informed decision-making in the Gambian food system has been scant, despite several sources of routinely-collected data being available. This descriptive study brings together data from four open-access global databases on food supply, political, economic, and demographic variables, and nutrition and health between 1990 and 2017 to study potential leverage points for improvement in the food system. It compares trends in food supply and nutritional outcomes in The Gambia against regional and global averages, and identifies potential drivers taken from a food systems framework. The data show that, over the past three decades, total energy supply has increased, and obesity is rising quickly, but iron deficiency persists in a proportion of the population. Overall diet composition is poor, with lower availability of fruit and vegetables and higher supply of sugar and oils compared to regional and global averages. Domestic production is low for most food groups and so a high dependence on imports from other countries bridges the gap in terms of energy supply. Measures of economic development, particularly GDP, were positively related with supply of cereals and animal source foods over time, but no such relationship was observed with fruit and vegetable supply. Food system policy to improve nutrition and health outcomes in The Gambia needs to focus on improving the diversity of food supply – especially fruit and vegetables - and maximizing national domestic production to reduce reliance on food imports. The use of open-source global datasets can be feasible in exploring food system characteristics and trends at the national level and could be applied in other contexts.